Implementasi Manajemen Fundrising Dan Distribusi Dana NU Care LAZISNU Ranting Tunggul Paciran Lamongan - Ahmad Badrut Tamam; Laila Alfun Nada (Al-Musthofa: Journal of Sharia Economics, 2024)
This research aims to find out how the management of fund raising and distribution of coin funds at NU CARE LAZISNU Ranting Tunggul Paciran Lamongan. The results of the research show that fundraising is carried out through the formation of coordinators in each region, there are cans distributed in each resident's house, each administrator has duties and responsibilities, fundraising is carried out door to door, information about collecting funds is online and offline. The distribution of the proceeds from the funds collected is still invested within the scope of NU and is focused on the Tunggul Village community, including annual activities to provide compensation for orphans during the month of Ramadan, educational scholarships, compensation for orphans and grief compensation.